Removal of Auramine O from Aqueous Solution Using Sesame Leaf: Adsorption Isotherm and Kinetic Studies - Liu, Li-E; Yu, Fei; Liu, Jindun; Han, Xiuli; Zhang, Haoqin; Zhang, Bing (Asian Journal of Chemistry, 2012)
The potential of sesame leaf was used to remove Auramine O from aqueous solution. The experiments were carried out under various conditions of solution pH, initial concentration, contact time, adsorbent dose, salt ionic strength and temperature. Adsorption isotherms were evaluated by the Langmuir, Freundlich and Redlich-Peterson isotherm models. The results of analysis indicated that the equilibrium data were fitted well with the Redlich-Peterson isotherm model. The maximum adsorption capacity of sesame leaf was found to be 249.2 mg g-1 at 293 K. The kinetic studies indicated that the pseudo-second-order equation is the best model that describes the adsorption behaviour. The thermodynamic parameters like DGº, DHº and DSº were calculated and the results indicated that the adsorption of Auramine O onto sesame leaf was a spontaneous and exothermic process in nature. This study implied that sesame leaf was a potential candidate as an economic biosorbent for the removal of Auramine O from aqueous solution.